Balance holes for dynamic stability of high-speed rotating machinery. (September 2022) - Hyeon, Seounghwan; Kim, Chiwon; Johnsen, Eric; Lee, Kwan-Soo
Abstract: Thrust balance system with balance holes is proposed for the dynamic stability of high-speed rotating machinery. The effects of the geometric variables on the leakage flow were identified numerically, and the heat transfer characteristics of the thrust bearing were analyzed. The leakage flow passing through the balance holes reduces the pressure in the thrust cavity and the axial thrust force acting on the rotating components by 26%, enhancing the dynamic stability. The dynamic performance can be calculated from a correlation that predicts the thrust force ratio, and thermal stability can be determined by predicting the cooling effect of the thrust bearing. In addition, a contour map is provided to evaluate the design feasibility of balance holes in various operating environments. Highlights: Flow and thermal characteristics in thrust cavity with balance holes were analyzed. Effects of balance holes on dynamic stability was identified by parametric study. Correlations were proposed to establish the design criteria of balance holes. Thrust force ratio was improved by up to 26% with ensuring thermal stability.